Implementasi Kebijakan Penumbuhan Kelompok Santri Tani Milenial di Bidang Pertanian (Studi di Balai Besar Pelatihan Peternakan Kota Batu) - Fahmi, Yahya; Wike, Wike; Amin, Fadillah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
As an agrarian country, Indonesia has significant potential for developing its agriculture sector. However, the majority of its agricultural workforce is elderly, and there is a lack of young talent entering the field, which has implications for the sustainability of agriculture in Indonesia. The issuance of PERKEMENPER 09/2019 has brought a breath of fresh air to the Indonesian agricultural sector through the millennial santri program. This research aims to assess the extent of the implementation of PERKEMENPER 09/2019 in Islamic boarding schools (pondok pesantren) with agricultural potential and promising conditions. This study employs a qualitative approach, using indicators adapted from Van Meter Van Horn, adjusted to the field conditions. The research results indicate that all three Van Meter Van Horn indicators (standards, resources, and external environment) show favorable outcomes. Islamic boarding schools and their students have made efforts to comply with PERKEMENPER 09/2019. Supporting resources have also been provided through human resource development programs and financial assistance. Additionally, the external environment, including the social and economic conditions in the city of Batu, is highly conducive to the implementation of these policies.